ANALYSIS OF THE LINEAR STABILITY OF THE ANISOTROPIC POROUS MEDIA IN ROTATING, SATURATE BY A NON NEWTONIEN FLUID SUBJECT TO THE ACTION OF THE CENTRIFUGAL BODY FORCE - VODOUNNOU, Edmond; AHOUANNOU, CLÉMENT; AKOWANOU, CHRISTIAN D.; DEGAN, GÉRARD (My University, 2014)
The present survey carries on the linear stability of middle in rotating anisotropic porous media saturated by a non-Newtonian fluid in an oblong cavity heated on the side submitted to the effect of the centrifugal force. The state of the marginal stability is established while determining the number of critical Rayleigh and the wave number of critical wave. We noted the effect of the anisotropic parameters
Keywords: Rotating porous anisotropic media; centrifugal force; linear stability; criticalRayleigh; doorstep of convection.